Analisis Herbarium Sebagai Media Pembelajaran pada Artikel Jurnal - Amelia, Riska Sari; Afryaningsih, Yunika; Purwaningsih, Dewi Ismu (HORIZON: Indonesian Journal of Multidisciplinary, 2024)
Learning media plays an important role in increasing the effectiveness of the educational process in elementary schools. An interesting alternative is to use a herbarium to support learning. A herbarium is a collection of plant specimens that have been dried and preserved in a form that can be studied by students. This research aims to analyze the effectiveness of using herbaria as a means of supporting learning in elementary schools to increase students' understanding of plant biodiversity and the importance of protecting the environment. This research uses qualitative methods combined with document research methods. Data was obtained by collecting articles and analyzing articles by researchers. The results of this research indicate that the use of herbarium as a learning medium in elementary schools can increase students' interest in learning about plants and the environment. Learners show higher involvement in the learning process, with direct observation of real plant specimens